2002
DOI: 10.1067/mcp.2002.124519
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic but not intestinal CYP3A4 displays dose‐dependent induction by efavirenz in humans

Abstract: Efavirenz is an inducer of liver CYP3A4 in healthy volunteers, and interpatient differences in magnitude of induction is partly explained by variation in systemic drug exposure. However, efavirenz did not appear to induce intestinal CYP3A4 or intestinal P-glycoprotein. These results suggest that drug interactions caused by induction of CYP3A4 can be liver specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
160
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(181 citation statements)
references
References 13 publications
18
160
3
Order By: Relevance
“…The possibility that TPM also induces the intestinal metabolism, which was not addressed in our studies, cannot be ruled out. Whereas most compounds that induce hepatic CYP3A4 also induce the intestinal enzyme, a few notable exceptions exist to this observation (18). Currently the unavailability of an appropriate in vitro tool to study intestinal CYP induction is a major limitation to investigating this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that TPM also induces the intestinal metabolism, which was not addressed in our studies, cannot be ruled out. Whereas most compounds that induce hepatic CYP3A4 also induce the intestinal enzyme, a few notable exceptions exist to this observation (18). Currently the unavailability of an appropriate in vitro tool to study intestinal CYP induction is a major limitation to investigating this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 12 women with epilepsy receiving stable dosages of valproic acid (VPA) along with a combination norethindrone, 1 mg/ethinyl estradiol, 35-µg tablet, TPM administered at doses of 200 mg/day, 400 mg/day, and 800 mg/day caused a statistically significant dose-related increase in the mean oral serum clearance (CL/F was 14.7-33% higher) of ethinyl estradiol (2). The mean C max value for ethinyl estradiol decreased by [15][16][17][18][19][20][21][22][23][24][25].4%, and the area under the curve (AUC 0−24 ) decreased by 18-30% at the 200-to 800-mg/day dose level. The pharmacokinetics of norethindrone remained unchanged.…”
mentioning
confidence: 99%
“…However, it is unlikely interactions between PIs and P-gp play a role in this phenomenon. Recent studies showed that efavirenz was not a P-gp substrate on P-gp-expressing LS180 V cells [30], nor did it modulate intestinal P-gp expression in healthy volunteers [31]. There are two possibilities:…”
Section: Discussionmentioning
confidence: 99%
“…According to a pilot clinical study [31], there was no correlation between efavirenz systemic exposure and CYP3A4 activity in healthy volunteers. An intensive in vitro study indicated the efavirenz is metabolized by CYP2B6 with some involvement of CYP3A [3].…”
Section: Discussionmentioning
confidence: 99%
“…The result can be obtained in <1 h and provide a reliable and reproducible measure of liver CYP3A4 activity and of the effect of modulators on the basal activity of the enzyme in humans. The ERMBT has been extensively used to evaluate the role of liver CYP3A4 activity in the pharmacokinetics of numerous drugs, including the anticancer agent docetaxel [19], the immunosuppressant ciclosporin [20], the antibiotic rifampin [21] and more recently the human immunodeficiency virus (HIV) non-nucleoside reverse transcriptase inhibitors delavirdine [22] and efavirenz [23].The ERMBT also reliably described the effects of inducers and inhibitors on liver CYP3A4 activity [21][22][23]. In addition, in a recent study conducted in HIV-infected patients [24], the ERMBT results correlated with the in vitro inhibition of CYP3A4 by the Liver 3A4 and P-gp in gefitinib-phenytoin interaction Br J Clin Pharmacol / 68:2 / 227 HIV-protease inhibitor nelfinavir.…”
mentioning
confidence: 99%